2015
DOI: 10.1080/1540496x.2015.1016842
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Illiquidity Premium in the Korean Stock Market

Abstract: We study the relation between the illiquidity premium and economic states in the Korean stock market. We find that aggregate market liquidity improves following real economic expansions and expansive monetary states and worsens after economic recessions and restrictive monetary states. The improved liquidity in the expansion-expansive state generates a huge illiquidity premium, while an illiquidity premium does not exist in the recession-restrictive state. As a result, the observed illiquidity premium displays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
8
8
0
Order By: Relevance
“…On the other hand, the average total liquidity premium during bear market, computed analogously to the average total liquidity premium during bull market, is equal to 0.24% monthly. Although insignificantly, total liquidity premium during bull market is higher than during bear market, supporting the previous results of Jang et al (2015) for the Korean stock market. Jang et al (2015) found that expansion-expansive state (good economic conditions) generate huge liquidity premium, while such a premium does not exist in the recession-restrictive state (bad economic conditions).…”
Section: Liquidity Premium During the Bull And The Bear Marketsupporting
confidence: 86%
See 4 more Smart Citations
“…On the other hand, the average total liquidity premium during bear market, computed analogously to the average total liquidity premium during bull market, is equal to 0.24% monthly. Although insignificantly, total liquidity premium during bull market is higher than during bear market, supporting the previous results of Jang et al (2015) for the Korean stock market. Jang et al (2015) found that expansion-expansive state (good economic conditions) generate huge liquidity premium, while such a premium does not exist in the recession-restrictive state (bad economic conditions).…”
Section: Liquidity Premium During the Bull And The Bear Marketsupporting
confidence: 86%
“…Although insignificantly, total liquidity premium during bull market is higher than during bear market, supporting the previous results of Jang et al (2015) for the Korean stock market. Jang et al (2015) found that expansion-expansive state (good economic conditions) generate huge liquidity premium, while such a premium does not exist in the recession-restrictive state (bad economic conditions). However, Jang et al's (2015) results indicate that liquidity premium displays strong state-dependent variations, while our study does not confirm that.…”
Section: Liquidity Premium During the Bull And The Bear Marketsupporting
confidence: 86%
See 3 more Smart Citations